2000
DOI: 10.1136/gut.47.5.612
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for dysplastic Barrett's oesophagus: a prospective, double blind, randomised, placebo controlled trial

Abstract: Background and aims-Photodynamic therapy (PDT) is a treatment in which cell damage is achieved by the action of light on a photosensitising agent. We have assessed the potential use of PDT in the ablation of Barrett's oesophagus. Methods-Thirty six patients with dysplastic Barrett's oesophagus receiving acid suppression medication with omeprazole were randomised to receive oral 5-aminolaevulinic acid (ALA) 30 mg/kg or placebo, followed four hours later by laser endoscopy. Follow up endoscopy was performed at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
133
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 17 publications
1
133
0
4
Order By: Relevance
“…[5][6][7] Most commonly used ablative therapies are argon plasma coagulation and photodynamic therapy. [8][9][10][11][12][13][14][15][16][17] However, success rates of these therapies vary and complete ablation is not achieved in all patients. Further, residual BE may be present after ablation in at least one-third of the patients and may be hidden underneath the restored squamous epithelial lining.…”
mentioning
confidence: 99%
“…[5][6][7] Most commonly used ablative therapies are argon plasma coagulation and photodynamic therapy. [8][9][10][11][12][13][14][15][16][17] However, success rates of these therapies vary and complete ablation is not achieved in all patients. Further, residual BE may be present after ablation in at least one-third of the patients and may be hidden underneath the restored squamous epithelial lining.…”
mentioning
confidence: 99%
“…The reported rate of successful ablation of combined low grade dysplasia or Barrett's esophagus itself ranges from 82% to 100%, and successful ablation rate in high grade dysplasia or cancer was 77% to 91% (Table 3). 9,[12][13][14][15][16] However, these studies confirmed the feasibility, safety of the PDT, and obtained mixed success as well in terms tumor response. Some report complete histologic response in "advanced" tumors, whereas others report only partial response even in "early" tumors.…”
Section: Omp Alone 31%mentioning
confidence: 80%
“…Several cases of unexplained sudden death after ALA PDT were also reported at the recent International Photodynamic Association congress (Munich, Germany, June 2005). Less penetrating green light (514 nm) has also been successfully used in combination with ALA and porfimer sodium with correspondingly less effective rates of ablation [94,95].…”
Section: Barrett's Esophagusmentioning
confidence: 99%